Sistem Informasi Geografis Pencarian Lokasi Wisata Kuliner Terdekat di Kota Mataram Berbasis Website - Julianto Eko Prasetyo; Ida Bagus Ketut Widiartha; Moh. Ali Albar (Journal of Computer Science and Informatics Engineering (J-Cosine), 2017)
Culinary development in the area of Mataram city at the moment is growing rapidly. Culinary tour offered varies greatly among them is the famous Lombok's cuisine with a taste of spiciness. The constraints experienced by travellers who have recently visited the city of Mataram is the difficulty to find a desired culinary location. Geographic information system for searching the location of nearby culinary Mataram city in this case can help make it easier for tourists to know the mapping of the location of the culinary tourism in the area of the city of Mataram. Web-based geographic information system is built by using the concept of MVC with directions from the position of travellers to culinary tour you want. The calculation to determine the distance of the location of culinary positions with travelers using the haversine formula. Based on a test that is done to the user, the average percentage of answers given by respondents agreed by 50% and the average percentage of answer strongly agree of 44.6% stating that geographic information systems this can already detect the locations of your users are able to display the distance between the user location information with location of culinary around, it can display the route to culinary tourism is selected and has the look of an attractive and easy to use. Keyword : Culinary, haversine, geographic information system, MVC.